Innovations in Practice: Dialectical behaviour therapy for adolescents: multisite implementation and evaluation of a 16‐week programme in a public community mental health setting. Issue 1 (17th September 2018) - Flynn, Daniel; Kells, Mary; Joyce, Mary; Corcoran, Paul; Gillespie, Conall; Suarez, Catalina; Swales, Michaela; Arensman, Ella
Abstract : Background: Dialectical behaviour therapy for adolescents (DBT‐A) is an intervention with a growing evidence base for treating adolescents with emotional and behavioural dysregulation. This study describes the implementation and effectiveness of 16‐week DBT‐A across multiple sites in publicly funded child/adolescent mental health services (CAMHS) in Ireland. Method: The Consolidated Framework for Implementation Research was used to guide this national implementation. Fifty‐four clinicians from seven CAMHS teams completed DBT training and delivered the 16‐week DBT‐A programme. Eighty‐four adolescents with emotional and behavioural dysregulation participated in the intervention and outcome measures were administered at preintervention, postintervention and 16‐week follow‐up. Results: Significant reductions on all outcome measures were observed for DBT‐A participants including presence and frequency of self‐harm, suicidal ideation and depression. Reductions in the number of acute inpatient admissions, bed days and emergency department visits were also reported. Conclusions: DBT‐A can be successfully implemented in CAMHS settings and yield positive outcomes for adolescents with emotional and behavioural dysregulation.